1991
DOI: 10.1093/ndt/6.12.971
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Cefuroxime and Ceftazidime in Patients with Acute Renal Failure Treated by Continuous Arteriovenous Haemodialysis

Abstract: To determine appropriate doses of cefuroxime and ceftazidime for septic patients with acute renal failure (ARF) treated by continuous arteriovenous haemodialysis (CAVHD), we performed pharmacokinetic studies in patients receiving these antibiotics. All patients were treated by CAVHD using Hospal AN69S 0.43 m2 filters and Fresenius 1.5% peritoneal dialysis fluid at dialysate flow rates (Qd) of 1 and 2 l/h. Patients received cefuroxime 500 mg (n = 11) or 750 mg (n = 1), or ceftazidime 500 mg (n = 9) i.v. 12-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…Since net Q UF ranged from 3.0 to 9.2% of nominal Q DI during the CVVHD segment of this study, the observed ceftazidime clearances predominantly reflect the effects of alterations in blood and dialysate flow on diffusion across the membrane. Unfortunately, the previously published studies of ceftazidime clearance during CVVHD did not control ultrafiltration rate to this degree, and thus their results cannot be directly compared to our observations (6,27). Furthermore, ceftazidime clearance by CVVHD has been previously evaluated with only the AN69 filter.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Since net Q UF ranged from 3.0 to 9.2% of nominal Q DI during the CVVHD segment of this study, the observed ceftazidime clearances predominantly reflect the effects of alterations in blood and dialysate flow on diffusion across the membrane. Unfortunately, the previously published studies of ceftazidime clearance during CVVHD did not control ultrafiltration rate to this degree, and thus their results cannot be directly compared to our observations (6,27). Furthermore, ceftazidime clearance by CVVHD has been previously evaluated with only the AN69 filter.…”
Section: Discussioncontrasting
confidence: 63%
“…The disposition of ceftazidime (6,12,27) during CVVH has been reported in single case reports or as a series of clinical cases. Unfortunately, it is difficult, if not impossible, to control the critical variables that may affect the clearance of ceftazidime in acutely ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some clinical data on the removal of ceftazidime by CRRT [2,[11][12][13][14][15] , but it is difficult to compare data from different forms of CRRT because the mechanism of drug removal in hemofiltration (i.e., drug removal by convection) differs from that of hemodiafiltration (i.e., removal by convection plus diffusion) [16] . There are also differences in flow rates, dose regimens and membranes used in the studies mentioned above.…”
mentioning
confidence: 99%